Value (Co)Creation by Means of Online Freelancing in SMEs - Pashkevich, Alena (My University, 2019)
Online freelancing is a growing employment trend of the last decade and gradually deserves more attention of both researchers and practitioners. This paper addresses the question how online freelancers (co)create value with their clients (SMEs). The examined literature required to unfold a coherent pre-understanding of the phenomenon comprises theories devoted to a flexible workforce, human resource management, outsourcing, and value creation. The qualitative data was obtained through semi-structured open-ended interviews and analyzed using grounded theory methodology. The participants were selected among regular users of a popular online platform that connects the freelancers with clients. The results of the paper are summarized in the conceptual framework being the first attempt to conceptualise the value co-creation between the freelancers and their clients. The study supports a customer-centric view on value co-creation and prescribes to the customer a value initiator, value creator, and the only value consumer and estimator roles. Nevertheless, it is concluded that the co-creation of value indeed takes place and the contribution of freelancers should not be ignored. Findings of the study indicate that SMEs face a strategic choice when start to externalise their tasks. By defining the strategy towards freelancing (cost cutting vs. strategic sourcing) SMEs determine their value focus (direct vs. returned value), approach to the flexible workforce (freelancer as a tool, freelancer as an expert, and freelancer as a team member), and roles the parties play in value co-creation process. The current paper contributes to the theoretical understanding of freelancing, SME’s behavior, and value co-creation, while explores the working process of SMEs with freelancers in practice and suggests how the latter can be utilised by the companies to bring value.
Keywords: online freelancing, freelance, value creation, value co-creation, externalised workforce